Mitochondrial Translocation of P66Shc Aggravates Cisplatin-induced AKI by Promoting Ferroptosis - Yang, Ming; Liu, Yu-ting; Han, Ya-chun; Zhang, Wei; Zhang, Hao; Yang, Shikun (Current Medicinal Chemistry, 2023)
Objective: The objective of this study is to evaluate the regulatory mechanism between P66Shc and ferroptosis in cisplatin-induced acute kidney injury (CP-AKI). Methods: A CP-AKI model was constructed both in vivo and in vitro using C57BL/6 mice and HK-2 cells, respectively. Renal histopathological injury, reactive oxygen species (ROS), and apoptosis were detected. Some parameters of ferroptosis (e.g. 4HNE and GPX4) and the expression of P66Shc/ P-P66Shc both in mitochondria and cytoplasm were tested. In in vitro studies, HK-2 cells were incubated with CP (50 uM); additionally, Fer1 and P66Shc siRNA were applied to explore the molecular regulatory mechanism of P66Shc in ferroptosis. The levels of mitochondrial ROS, apoptosis and the expression of 4HNE,GPX4, P66Shc, and P-P66Shc were tested. Furthermore, the mitochondrial translocation of P66Shc was detected. Results: CP treatment caused elevation of Scr, BUN and renal MDA levels and decreased renal SOD, GSH-PX and GPX4 levels. CP enhanced the expression of 4HNE, P66Shc and P-P66Shc both in vivo and in vitro. Renal oxidative stress and apoptosis were significantly increased in CP-AKI mice. Electron microscopy examination indicated obvious mitochondria injury in renal tubular cells of CP-AKI mice. The level of ferroptosis and the translocation of P-P66Shc from the cytoplasm to mitochondria were significantly increased in HK-2 cells under CP condition, and these effects were obviously blocked by P66Shc siRNA treatment. Conversely, pretreatment with the ferroptosis inhibitor (Fer1) had no effect on the expression and mitochondria translocation of PP66Shc under CP condition. Conclusion: Mitochondrial translocation of P66Shc could result in mitochondrial injury and lipid peroxide accumulation, which ultimately led to ferroptosis and aggravated CPinduced AKI.
Keywords: AKI